PENANGGUHAN PENAHANAN TERHADAP TERDAKWA DALAM PROSES PEMERIKSAAN PERSIDANGAN DITINJAU BERDASARKAN ASAS PERSAMAAN KEDUDUKAN DALAM HUKUM - Gusti Heliana Safitri; Ari Saputra (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The granting of suspension of detention in each level of examination must remain based on the principle of quick, simple, and low-cost justice. Keeping all the risks that occur namely the escape of the suspect / defendant in the examination process is an effort so that the judicial process is fast (does not take a long time), simple (not convoluted) and low costs (the use of cost-effective case). Based on the due process model that requires fair and fair treatment by law enforcement agencies or institutions to all suspects / defendants, the partiality in the form of discriminatory treatment in the trial process of the suspect / defendant is a violation of the principle of equality before the law. which is an ideal desired by the community if it is violated, then the resulting legal product will lose its meaning. Guaranteed legal protection is implied in the principle of Equality Before the Law, which is not only a guarantee of getting the same treatment but also a guarantee that the law will not give privileges to other legal subjects. Because if this happens then it can violate the principles of Equality Before the Law and encourage the creation of discrimination before the law. The criminal justice system is based on the principles of being the guardian of the Indonesian criminal justice.